Energy Efficiency of a Small Bioreactor in Various Climatic Zones - V. g Isakov; A. A. Abramova; M. Yu. Dyagelev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
The authors proposed a model for estimating the heat balance and energy efficiency of a bioreactor that makes possible for a small-sized reactor operating on a relatively low-energy substrate to determine the critical volume, under which the existing climatic conditions allow year-round fully autonomous operation of the digester, as well as for evaluation the potential energy efficiency of such a bioreactor (output commodity heat). For the numerical characteristics of the climatic zone, it is proposed to use the average annual temperature and/or the “degree-day of the heating period” (DDHP) indicator common in construction heat engineering; the DDHP value more adequately characterizing the unevenness of the average monthly temperature distribution, i.e. degree of climate continentality. At the same time, the value of the critical volume of the bioreactor, at which year-round autonomous operation of the digester operating on the municipal sewage sludge, is possible, varies from 7.5 (Vladikavkaz, DDHP = 3410) to 17.0 m3 (Tomsk, DDHP = 6938), i. e. increases almost in proportion to the degree-day of the heating period. It should be noted that when using a substrate with a high biogas yield, e. g., pig manure (a biogas yield of 40 g/kg is adopted), the critical volume in all cases is less than 1 m3. Such results are relevant only for relatively low-energy raw materials. The nature of changes in the output of commodity heat, depending on the volume of the bioreactor and climatic conditions, is quite expectable, viz. the amount of heat that is useful for business interests is higher, the higher is the reactor volume and the milder is the climate. However, when the reactor volume is less than 5 m3, the non-linearity of the graphs is much higher, i. e. for a designer of especially small bioreactors, it seems mandatory to carry out such calculations. The obtained numerical values can be useful both for the designer of bioreactors and for the customer of the project when evaluating the economic efficiency of the planned new innovations.